Response to recurrent selection for resistance to Striga hermonthica (Del.) Benth in a tropical maize population - Menkir, A.; Kling, J. (Wiley, 2007)
Striga hermonthica (Del.) Benth is an obligate root parasite infecting maize (Zea mays L.) and causing considerable yield losses in Africa. Few studies have been conducted to determine the effectiveness of recurrent selection for improving resistance to S. hermonthica in maize. The objective of this study was to evaluate genetic gain achieved in a composite subjected to six cycles of selection under S. hermonthica infestation. The selection cycles and checks were evaluated with and without S. hermonthica infestation at two locations in Nigeria for 2 yr. Selection for improved performance under S. hermonthica infestation significantly increased grain yield by 24% cycle-1 and ears per plant by 9% cycle-1. At the same time, the gain per cycle was −7% for relative yield loss, −5% for host damage rating, −9% for emerged S. hermonthica plants, −4% for anthesis–silking interval, and −5% for ear aspect. Selection under S. hermonthica infestation was accompanied by a concomitant increase in grain yield and improvement in plant aspect and ear aspect without S. hermonthica infestation. The observed progress in performance under S. hermonthica infestation demonstrates the effectiveness of recurrent selection for increasing polygenetic resistance against the parasite in tropical populations.